ダイ 43ジ ナンキョク チイキ カンソク ニ オケル ケンキュウ カンソク ニ カンスル カンソク ケンキュウ ショウシュウカイ センヨウ カンソクセン ニヨル ナンキョクカイ カイヨウ カンソク ホウコク - 小達, 恒夫; オダテ, ツネオ; 福地, 光男; フクチ, ミツオ; Odate, Tsuneo; Fukuchi, Mitsuo (2002)
P(論文) 「第43次南極地域観測における研究観測に関する観測研究小集会-専用観測船による南極海海洋観測」を, 平成13年10月4日, 国立極地研究所講堂において開催した。本年度出発する第43次日本南極地域観測隊(43rd Japanese Antarctic Research Expedition, JARE-43)において実施される, 「専用観測船」による海洋観測参加者を中心に30名の参加者があった。本研究小集会では, 「専用観測船」航海乗船者へJARE参加の心構え及び安全対策の説明が行われた。併せて, 「専用観測船」での希望観測項目の詳細を打ち合わせ, 観測スケジュールが改訂された。 A workshop on "Marine Science Program in the 43rd Japanese Antarctic Research Expedition on a Charter Research Vessel" was held on 4th October 2001 at the convention hall of the National Institute of Polar Research with 30 participants. Most of the participants will join the research cruise organized by the 43rd Japanese Antarctic Research Expedition (JARE-43) using a charter vessel. One of the purposes of this workshop is to give detailed information on the JARE system. At the same time, safety guidelines for the cruise were explained. In addition, the work schedule for the cruise was revised based on detailed requests from the participants. departmental bulletin paper